Simeprevir with peginterferon/ribavirin for patients with hepatitis C virus genotype 1: high frequency of viral relapse in elderly patients - Watanabe, Takao (Springerplus, 2016)
PURPOSE: The tolerability and efficacy of simeprevir in combination with peginterferon and ribavirin in patients infected with hepatitis C virus (HCV) genotype 1 under actual clinical conditions were investigated. METHODS: A total of 176 patients with chronic HCV genotype 1 infection were treated with simeprevir for 12 weeks plus Peg-IFN/RBV for 24 weeks. Overall, 107 (60.7 %) patients were aged 60 years or more, and 16 (9 %) patients were aged 70 years or more. Treatment discontinuation, sustained virological response 12 (SVR12), and viral relapse were evaluated and compared between younger patients and elderly patients. RESULTS: The rates of undetectable HCV RNA at the end of treatment were 95.8, 100 and 93.1 % in treatment-naïve, prior relapse, and prior non-responders, respectively. However, the rates of SVR12 were 82.4, 88.2 and 69.2 %, respectively. Especially in prior non-responders, viral relapse was relatively frequent. Treatment discontinuation and SVR12 were not different between patients aged <70 and ≥70 years, but viral relapse after completing treatment was significantly more frequent in patients aged ≥70 years (p = 0.012). CONCLUSIONS: In simeprevir with peginterferon and ribavirin therapy, viral relapse was relatively frequent. Especially in elderly patients, the relapse rate was high after completing treatment, instead of low frequency of discontinuation by the adverse events.